Studi Laju Korosi Baja Tahan Karat Martensitik 13CR Setelah Proses Perlakuan Panas [Effect of Heat Treatment of AISI 410 Martensitic Stainless Steel on Microstructure and Corrosion Resistance] - Rizky Dwisaputro; Mochammad Syaiful Anwar; Rusnaldy Rusnaldy; Efendi Mabruri (National Research and Innovation Agency (BRIN), 2018)
Martensitic stainless steels are used in turbine blade materials in steam turbines of power plants. This study aims to determine the effect of heat treatment (austenitized and tempering) on microstructure and corrosion rate of AISI 410 martensitic stainless steel. The observation of microstructure was conducted using optical microscope and the corrosion test was performed in 3.5% NaCl solution which was carried out with Gamry G750 tool. The microstructure of AISI 410 steels after annealing process was composed of ferrite and metal carbide. The microstructure of martensite and retained austenite was obtained after the steel AISI 410 underwent a process of tempering at 600 °C with different austenitizing temperature. Meanwhile, the microstructure of temper martensite with retained austenite and metal carbide was found in AISI 410 steels after austenitized at 1050 °C with different tempering temperature. The corrosion rate of AISI 410 steels decreased with increasing austenitizing temperature. Meanwhile, very high corrosion current was found in AISI 410 steel at tempering of 550 °C and austenitized of 1050 °C. AbstrakBaja tahan karat martensitik telah digunakan pada material turbine blade pada turbin uap. Penelitian ini bertujuan untuk mengetahui pengaruh perlakuan panas quenching dan tempering terhadap struktur mikro dan laju korosi baja tahan karat martensitik AISI 410. Pengujian yang dilakukan adalah pengamatan struktur mikro menggunakan mikroskop optik dan uji korosi di dalam larutan 3,5% NaCl dengan alat Gamry G750. Struktur mikro baja AISI 410 setelah proses annealing adalah ferit dan karbida logam. Struktur mikro martensit dan austenit sisa dapat terbentuk bilamana baja AISI 410 telah mengalami proses tempering pada suhu 600 °C dengan suhu quenching yang berbeda. Sedangkan struktur mikro berupa tempermartensit dengan austenit sisa dan karbida logam ditemukan pada baja AISI 410 setelah quenching pada suhu 1050 °C dengan suhu tempering yang berbeda. Laju korosi baja AISI 410 semakin rendah seiring peningkatan suhu quenching. Sedangkan laju korosi sangat tinggi ditemukan pada baja AISI 410 pada suhu temper 550 oC dan quenching 1050 oC.